2022
DOI: 10.3390/children9121975
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Clinical Consequences, Prevention, and Treatment of Childhood Obesity

Abstract: Obesity might adversely affect the health and well-being of children and their families. Childhood obesity has crucial implications for health, both during childhood and as they age. It is highly associated with many acute problems and is commonly present during childhood, making visits and hospital admissions polarized in this group of children. The problems that may affect these children can be medical, such as asthma, chronic inflammation, orthopedic abnormalities, liver disease, diabetes mellitus or dyslip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 113 publications
0
16
0
7
Order By: Relevance
“…The escalating incidence of childhood obesity has emerged as a significant global public health issue ( 14 ). The prevalence of overweight or obese children and adolescents aged 5–19 years, has surged from 4% in 1975 to an alarming 18% in 2016 ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The escalating incidence of childhood obesity has emerged as a significant global public health issue ( 14 ). The prevalence of overweight or obese children and adolescents aged 5–19 years, has surged from 4% in 1975 to an alarming 18% in 2016 ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies and health-related reports from various countries have consistently demonstrated a significant surge in the prevalence of overweight and obesity among children and young adults over the past two decades ( 14 ). Research conducted in the United States ( 15 17 ), China ( 1 , 18 , 19 ), Denmark ( 20 ), England ( 21 , 22 ), Sweden ( 23 ), and Norway ( 24 ) has consistently documented a rapid escalation in obesity rates among children and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Obese children also exhibit anomalies during sleep, such as positive pharyngeal pressure and less pharyngeal dilatory activity [17]. Adenotonsillar hypertrophy is a significant risk factor for OSA in obese children, but surgical removal of tonsils may only have a partial effect on improving the condition [18]. Some studies report a significant reduction in lung function in obese children.…”
Section: Diet-induced Obesitymentioning
confidence: 99%
“…Prenatal and early postnatal factors increase the risk of developing obesity and several additional diseases throughout life [111,113]. Children born from mothers with obesity or from women who developed gestational diabetes are more likely to develop obesity and metabolic problems compared to children born from healthy mothers [113].…”
Section: The Multiple Causes Of Childhood Obesitymentioning
confidence: 99%